2012
DOI: 10.1371/journal.pone.0048423
|View full text |Cite
|
Sign up to set email alerts
|

Expression Levels of the ABCG2 Multidrug Transporter in Human Erythrocytes Correspond to Pharmacologically Relevant Genetic Variations

Abstract: We have developed a rapid, simple and reliable, antibody-based flow cytometry assay for the quantitative determination of membrane proteins in human erythrocytes. Our method reveals significant differences between the expression levels of the wild-type ABCG2 protein and the heterozygous Q141K polymorphic variant. Moreover, we find that nonsense mutations on one allele result in a 50% reduction in the erythrocyte expression of this protein. Since ABCG2 polymorphisms are known to modify essential pharmacokinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 46 publications
3
57
1
Order By: Relevance
“…Saison et al (2012) also suggested that the R236X polymorphism (706 C.T) may be the basis of the Jr(a2) blood type in Romani Gypsy diaspora communities of Southwestern Europe, and a homozygous R246X (736 C.T) variant has been found, resulting in Jr(a2) erythrocytes in two Caucasian individuals. Heterozygous R246X was shown to lower ABCG2 expression approximately 50% in vivo during flow cytometry analysis of erythrocytes (Kasza et al, 2012). Along with these studies, it is predicted that the E334X variant also produces the Jr(a2) blood group (Zelinski et al, 2012).…”
Section: Junior Blood Groupmentioning
confidence: 92%
See 1 more Smart Citation
“…Saison et al (2012) also suggested that the R236X polymorphism (706 C.T) may be the basis of the Jr(a2) blood type in Romani Gypsy diaspora communities of Southwestern Europe, and a homozygous R246X (736 C.T) variant has been found, resulting in Jr(a2) erythrocytes in two Caucasian individuals. Heterozygous R246X was shown to lower ABCG2 expression approximately 50% in vivo during flow cytometry analysis of erythrocytes (Kasza et al, 2012). Along with these studies, it is predicted that the E334X variant also produces the Jr(a2) blood group (Zelinski et al, 2012).…”
Section: Junior Blood Groupmentioning
confidence: 92%
“…The use of blood samples could be a welltolerated method of analyzing ABCG2 levels since it is noninvasive and quantifiable with good anti-ABCG2 antibodies. This method has been used to describe significant decreases in protein expression in heterozygous Q141K and R236X carriers (Kasza et al, 2012). This proved the method could be successful in showing the varying tissue levels of ABCG2 for differing genotypes.…”
Section: Perspectives For Future Researchmentioning
confidence: 95%
“…According to our previous experience, strongly reduced RBC expression levels of the ABCG2 [7] and the ABCB6 [8] membrane proteins were connected to specific mutations and/or polymorphisms in the coding genes. Therefore, we analyzed the DNA extracts of the blood samples of the volunteers with low RBCPMCA4b expression by Sanger sequencing of the ATP2B4 gene, coding for this protein.…”
Section: 3mentioning
confidence: 95%
“…RBC membrane protein determinations were carried out according to our recently developed method [6][7][8][9]. In brief, we fixed and permeabilized the RBC membranes by using 1% formaldehyde solution, resulting in RBC "ghosts", and then equal number of cells were incubated with the PMCA-specific primary antibody (JA3, mouse monoclonal antibody, RRID: AB 628160) followed by a secondary, Alexa Fluor 488 labeled goat anti-mouse (H + L) antibody (Thermo Fisher/Life Technologies), in 96 well plates.…”
Section: Rbc Membrane Protein Studiesmentioning
confidence: 99%
“…As published recently, we have developed a simple, rapid, reliable flow cytometrybased diag nostic assay for the quantitative determination of the membrane protein, ABCG2, in the RBC membrane [82]. By using specific antibodies, we could detect ABCG2 specifically and sensitively in RBCs.…”
Section: Rbc Membrane Proteins As Potential Biomarkersmentioning
confidence: 99%